A 16-year-old with borderline mucinous tumor of the left ovary - Saloni S. Zunzunwala; Vibha S. More; Pradnya Changede; Arun H. Nayak; Rachana Barkale; Ashwini Shinde (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Incidence of ovarian malignancy in children and adolescents is 1 to 1.5% with non-epithelial tumors being the most common type. Ovarian mucinous tumors commonly seen in third to sixth decade, are rarely seen in adolescents. Timely diagnosis and management are important to save patient’s life and fertility. We are presenting an interesting case of a 16-year-old girl with atypical borderline mucinous ovarian tumor.